African buffalo serum contain novel trypanocidal protein - Reduth, D.; Grootenhuis, J.G.; Olubayo, R.O.; Muranjan, M.; Otieno-Omondi, F.P.; Morgan, G.A.; Brun, R.; Williams, D.J.L. (Wiley, 1994)
ABSTRACT. The high ability of African buffalo, as compared to domestic cattle, to control infections with Trypanosoma brucei brucei IL Tat 1.4 organisms did not correlate with the timing or magnitude of parasite surface coat‐specific antibody responses and may have resulted from the constitutive presence in buffalo blood of a novel trypanocidal factor. Buffalo plasma and serum contained material that killed bloodstream stage T. b. brucei, T. b. rhodesiense, T. b. gambiense, T. evansi, T. congolense, and T. vivax organisms during four h of incubation at 37° C in vitro. Serum from eland was also trypanocidal whereas serum from oryx, waterbuck, yellow‐back duiker, cattle, horse, sheep, goat, mouse, rat, and rabbit was not trypanocidal. The buffalo serum trypanocidal material was not lipoprotein, or IgG, and had the following properties: 1) a density of < 1.24 g/ml determined by flotation ultracentrifugation; 2) insolubility in 50% saturated ammonium sulphate; 3) non‐reactivity with anti‐bovine IgM, and anti‐bovine IgG; 4) non‐reactivity with protein G, and protein A; 5) a relative molecular mass of 152 kDa determined by chromatography on Sephacryl S 300, and of 133 kDa determined by chromatography of the 50% SAS cut of IgG‐depleted buffalo serum on Superose 12; 6) no associated cholesterol; and 7) inactivation by digestion with proteinase K that was immobilized on agarose.